COMPETENT APPROACH IN EDUCATION: THEORETICAL AND PRACTICAL CONCLUSIONS - Ulmasjon Khusniddinovich Totliyev (Bright Mind Publishing, 2025)
Education based on a competency-based approach does not require students to develop knowledge, skills and abilities separately, but to acquire them comprehensively. Accordingly, teaching methods will also change. The basics of choosing and constructing teaching methods in the competence approach were considered. For this, the concepts of competence and competence were clarified. Its structure and function were defined. Then, after the construction of the design technology of basic and subject-related competences, the principles of choosing teaching methods are derived from this approach. In the article, the above-mentioned theoretical ideas are proved in practice.
Keywords: Educational competence, Competency-based learning, Cognitive activity, Interdisciplinary integration, Health education.